1999
DOI: 10.1101/gad.13.14.1780
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism between Goalpha and Gqalpha in Caenorhabditis elegans: the RGS protein EAT-16 is necessary for Goalpha signaling and regulates Gqalpha activity

Abstract: To elucidate the cellular role of the heterotrimeric G protein G o , we have taken a molecular genetic approach in Caenorhabditis elegans. We screened for suppressors of activated GOA-1 (G o ␣) that do not simply decrease its expression and found mutations in only two genes, sag-1 and eat-16. Animals defective in either gene display a hyperactive phenotype similar to that of goa-1 loss-of-function mutants. Double-mutant analysis indicates that both sag-1 and eat-16 act downstream of, or parallel to, G o ␣ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
172
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(189 citation statements)
references
References 64 publications
15
172
1
1
Order By: Relevance
“…Mutation of both the IP 3 receptor ITR-1 (Baylis et al, 1999;Dal Santo et al, 1999) and the DAG kinase DGK-1, essential for reduction of DAG levels (Hadju-Cronin et al, 1999;Nurrish et al, 1999), strongly reduced avoidance after preexposure, but did not affect chemoattraction to 0.1-100 mM NaCl or avoidance of 1 M NaCl ( Figure 6C and D, results not shown). This indicates that IP 3 and DAG signalling are only involved in the plasticity response.…”
Section: Gustatory Plasticity Requires Ca 2 þ Signallingmentioning
confidence: 97%
“…Mutation of both the IP 3 receptor ITR-1 (Baylis et al, 1999;Dal Santo et al, 1999) and the DAG kinase DGK-1, essential for reduction of DAG levels (Hadju-Cronin et al, 1999;Nurrish et al, 1999), strongly reduced avoidance after preexposure, but did not affect chemoattraction to 0.1-100 mM NaCl or avoidance of 1 M NaCl ( Figure 6C and D, results not shown). This indicates that IP 3 and DAG signalling are only involved in the plasticity response.…”
Section: Gustatory Plasticity Requires Ca 2 þ Signallingmentioning
confidence: 97%
“…In the presence of food (Escherichia coli is used as a food source in the laboratory), pharyngeal pumping (7,8), egg laying (8,9), and male mating (10) are increased, whereas locomotion is decreased (11). Conversely, in the absence of food, the opposite behaviors are observed.…”
mentioning
confidence: 93%
“…Therefore, we tested the participation of these RGS proteins and GPB-2 in adaptation. As a result, two eat-16 alleles, eat-16(ce71) (40) and eat-16(sa609) (24), which are putative null and loss-of-function mutants, respectively, and animals carrying a high-copy array of the egl-10 gene nIs51 (37) showed modest defects in adaptation (Fig. 4C).…”
Section: (ϩ)]mentioning
confidence: 99%
“…Previous reports have shown that GOA-1 and EGL-30 antagonistically regulate acetylcholine release at neuromuscular junctions (24)(25)(26)(27). Hence, we hypothesized that EGL-30 also has an effect opposite to GOA-1 in adaptation.…”
Section: Goa-1 Acts In Awc Chemosensory Neurons For Olfactory Adaptatmentioning
confidence: 99%
See 1 more Smart Citation